CowParade New York : The Cows, The Artists, The Spectacle. Over 300 Moovers & Shakers. - Craughwell, Thomas; Elbaum, Jerry; Giuliani, Rudolph W. (New York : Workman Publishing Company Inc., 2000)
Sacred Cow #5 at the Central Park Zoo. Cowabunga at the South Street Seaport Flags at the UN and Mooodama Butter-fly in Lincoln Center. It was the summer the cows took over New York. Pawing, grazing, stomping and stampeding, they transformed the city into a festival of bovinely inspired art. CowParade is the creator of summer-long, city-wide public art projects that bring artists, corporations, and cows together to delight residents and visitors and raise money for charity. Previous CowParades have appeared in Chicago and Zürich, Switzerland.
Adams, Robert ; Anusewicz, Colette ; Armock, Amy ; Banziger, Nolde ; Barolini, Nicoletta ; Barton, G. ; Basirico, Patricia ; Baxter, Dan ; Bayer, Candida ; Beckett, Holly ; Beispel, Allison ; Bendis, Keith ; Bethel Arts Junction ; Billy, André ; BBissell, C. ; Blackwell, Marjorie ; BooCrew Productions ; Booth, Jennie ; Bozell ; Braun-Reinitz, Janet ; Britto, Romero ; Brooklyn Model Works ; Brucker-Cohen, J. ; Brunelle, Jim ; Burns, Ron ; Cadiz, Edwin G; ; Campbell, Naomi ; Carew, Colin ; Cesana, Andy ; Castelluccio, Federico ; Chan, Cynthia ; Chavchavadze, Sasha ; Chevallier, Georges P. Le ; Children of the Neighborhood ; Christie, Robert ; Christopher, Tom ; Chu, Tim ; Clark, Ursula ; Cogan, Orly ; Colossi, Joseph ; Connolly, E. ; Conroy, Jeffrey ; Creative Team at the NBC agency ; Crocket Effects ; Cusack, Margaret ; Dean, Jason ; DeCesare, Jim ; DeMasi, Orianna ; Dennan, Mike ; Dolack, Linda ; Douglas, Laurie ; Dunlop, David ; Eastman, Jon ; Edelstein, Barbara ; Eisenberg, Linda ; Elrod, Biff ; Erhardt, A. ; Falkowitz, Alice ; Feder, Elizabeth ; Feder, Terry Donsen ; Fernandez-Stein, Silvia ; Foca, Pam ; Fogel, Jacqueline ; Foster-Hall, Charles ; Freda, Anthony ; Freedman, Jacqueline ; Freedman-Shea, Diana ; Frund, Kathryn ; Gaeta, Pattie ; Gale, Cynthia ; Galluccio, Joseph A. ; Garance ; Garnett, Sandy ; Garro, Mark ; Gaydos, Tim ; Geller, Matthew ; Geppetto Studios Inc. ; Gifford, Jessie ; Gilman, Randy ; Giovanopoulos, Paul ; Golbert, Sandra ; Goldberg, Caryn ; Golio, Gary ; Gordon, Janine ; Grondahl, Corinne ; Grooms, Red ; Guerra, Arthur ; Guerra, Homer ; Haas, Richard ; Hanauer, Ellen ; Hanke, Bruce ; Harman, Fred ; Healy, Julia ; Hei-Art ; Henderson, Kris ; Henri Bendel Visual Team ; Ho, R. ; Holmer, Martie ; Hope169 ; Howard, Ron ; Hung, Kuo Chih ; etc.
Engels
CowParade New York 2000, New York, 2000
boek
Keywords: New York